POLA KOMUNIKASI PEGAWAI HELPDESK DALAM MELAYANI WAJIB PAJAK PENGGUNA E-FAKTUR DI KANTOR PELAYANAN PAJAK PRATAMA PEKANBARU TAMPAN - Humnah Rafidah; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The development of communication technology nowadays has a big influence on everyday life. Developing technology makes it easier for people to obtain information. Along with the development of technology, the Directorate General of Taxes continues to carry out digital transformation to improve service quality and increase the effectiveness of monitoring the needs of taxpayers. The E-Invoice application is a form of modernization in the form of tax services. People who do not fully understand the E-Invoice application can consult directly at the helpdesk service assistance corner. To maintain service quality, an effective communication pattern between taxpayers and helpdesk employees is required in consultation. Therefore, the problem to be examined in this study was about the Communication Patterns of Helpdesk Employees in Serving Taxpayers using E-Invoice Users at the Tampan Pekanbaru Tax Office.This study used descriptive qualitative research methods to describe the state of the subject and research object following the existing field conditions. There are 7 informants in this study based on purposive technique. Data collection was carried out through observation, interviews, documentation. The data were validated using the extension of participation and triangulation data.The results of this study were: 1) the communication that exists between taxpayers who use E-Invoice and helpdesk employees occurs because there is a cause-effect or action-reaction process, which has alternating directions; 2) The communication patterns contained in this study are interaction or interactional communication patterns. The purpose of communication is to reduce the taxpayers of E-Invoice users coming to consult helpdesk employees with the same error; 3) barriers to communication between helpdesk employees and taxpayers are barriers to differences in culture, ethnicity, race, religion and language, age vulnerability, language intonation, and environmental conditions that are not conducive to hindering the communication process. Based on these results, it is concluded that the organizational communication pattern at the Primary Tax Office uses an interactional pattern. Keywords: E-Facturer, Tax, Communication Patterns